Legal Responsibilities of Online Delivery Service Entrepreneurs as Intermediate Consumers for Obscurity Concert Ticket Information - Ni Putu Sawitri Nandari; Ida Ayu Sadnyini; Dewa Krisna Prasada; Kadek Julia Mahadewi; Bellya Lulu'il Husna (Fakultas Hukum, Universitas Warmadewa, 2024)
In the current era of digitalization, where information technology continues to develop, accompanied by the competitive demands of the technology-based business world, new business ideas are being seen which are seen as great opportunities by business people. One of the businesses that is currently very popular is the online entrustment service business for purchasing concert tickets via Instagram. The purpose of this research is to determine and analyze the legal responsibility of online entrustment service entrepreneurs who default on consumers due to unclear concert ticket information and related forms of legal protection for consumers for unclear information by online entrustment service entrepreneurs in purchasing concert tickets via Instagram. The research method used is normative juridical using legal materials obtained from primary, secondary and tertiary legal materials. The existence of a breach of contract regarding unclear concert ticket information carried out by online entrustment service entrepreneurs on Instagram means that jastip entrepreneurs who violate the agreement can be held responsible for compensating consumers for losses with sanctions as regulated in the relevant regulations. Therefore, this creates the creation of consumers' rights to obtain legal protection, both preventively and repressively, where in order to realize this legal protection it is also necessary to have joint synergy between the government, society, institutions and related parties.